Microbiological Characteristics (TPC and E coli) in Frozen Tuna Loin (Case Study at PT Yakin Pasifik Tuna - Zahleka, Tuti; Ukhty, Nabila; Hafinuddin, Hafinuddin; Rozi, Anhar (Jurnal Perikanan Terpadu, 2024)
The aim of this research was to examine the microbiological characteristics (TPC and E. coli) of frozen tuna loin in the case study of PT. Yakin Pasifik Tuna Banda Aceh. This study uses a quantitative descriptive method, which describes the test results obtained in the laboratory on the object being tested. The samples used in this study were frozen tuna loin and fresh tuna loin. The TPC in frozen tuna loin was 3.6 x 104 CFU/gram, which still meets the standards of SNI 4104:2015. Meanwhile, the results of the TPC microbial contamination test on fresh tuna was 7.0 x 103 CFU/gram or which still meets the standards of (SNI 7530.1:2009).  The E coli value in frozen and fresh loin was obtained with a value of <3. This result is in accordance with SNI 4104:2015 and SNI 7530.1:2009. In conclusion, fresh tuna loin meets SNI 7530.1:2009 while frozen tuna loin meets SNI 4104:2015.